How much capacity deferral value can targeted solar deployment create in Pennsylvania?. (November 2019) - Keen, Jeremy F.; Apt, Jay
Abstract: We assess the ability of distributed solar to defer distribution capacity projects in a typical low load growth utility in the Northeast USA, PECO. We find that targeted placement can increase the deferral value of solar up to fourfold, but that deferrable projects are rare. In our baseline scenario, we find a 5% solar energy penetration with Net Energy Metering rolled out from 2020 to 2030 would increase rates by 0.8% over a 20-year horizon and generate just $1 MM in net present deferral value. This estimate assumes untargeted placement of solar, a low effective capacity (i.e. the reduction in peak load relative to solar's nominal capacity), a 1% growth rate, and 1% of PECO's distribution yearly capex budget that is deferrable. A higher effective capacity (e.g. from coupling energy storage with solar) and targeted placement could generate a net $8 MM of value over the same horizon, but the rate increase is mostly unaffected. We recommend the use of targeted solar placement in utility planning processes. Compared to untargeted placement, targeted placement can increase the total deferral value fourfold, but the effect on rates is small for PECO because few capacity deferral opportunities exist. Highlights: Untargeted solar misses chances for capacity deferral and has short deferral times. Targeted solar placement can increase the capacity deferral value by a factor of 4. Solar with energy storage increases deferral value mainly at low penetrations. Solar's deferral value is largest when occasional overloading is allowed. Capacity deferral opportunities are uncommon for PECO and unlikely to affect rates.